What is Social Innovation? - Westley Frances (Waterloo Institute for Social Innovation and Resilience, 2014)
Changing the system dynamics that created the problem in the first place "A social innovation is any initiative (product, process, program, project, or platform) that challenges and, over time, contributes to changing the defining routines, resource and authority flows or beliefs of the broader social system in which it is introduced. Successful social innovations have durability, scale and transformative impact. (Frances Westley 2014)